EDUKASI TEKNIK MENGGOSOK GIGI YANG TEPAT UNTUK MENCEGAH MASALAH GIGI DAN MULUT DI SDN MOJOSARI, KECAMATAN MANTUP, KABUPATEN LAMONGAN - Mahfud, Muhammad; Mulyadi, Mulyadi; Havidah, Nur; Khotimah, Tri Mulya Husnul; Rosyidah, Ulfatur; Rikza, Muhammad (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (PkM)is a form of student service to the community in various fields, one of which is the health sector. A health problem that often occurs in society, especially children, is a lack of awareness and understanding about dental and oral health. This research aims to analyze the implementation of dental health education in the PkM program at SDN Mojosari using the Asset-Based Community Development (ABCD) approach. This approach focuses on utilizing the assets and potential of the community to support the sustainability of dental health education.  The methods used include observation, interviews and documentation during extension activities. The results of the research show that this counseling has a positive impact because it can increase students' awareness of the importance of maintaining healthy teeth by brushing their teeth with good and correct techniques. Apart from that, this program has succeeded in utilizing local resources such as health workers and teachers as agents of change in dental health education. Thus, the ABCD approach has proven effective in developing extension programs that are sustainable and based on community strengths.